منهجية إصلاح المجتمع في ضوء السيرة النبوية(صلى الله عليه وسلم) دراسة من خلال الشيخ الندوي (رحمه الله) - ADIL SHAH, (Seerat Studies, 2025)
Abstract The methodology of Sheikh Abu Al Hasan Ali Al-Nadawi(رحمہ اللہ) in explaining the reform of social interaction through the Prophet’s (ﷺ) biography is based on self-purification, practical example, mercy, justice, consideration of people’s natures, and presenting the complete Prophetic model that reforms individuals and societies. In his writings on the Prophet's(ﷺ) biography, Sheikh Abu al-Hasan Ali Al-Nadawi (رحمہ اللہ) presents a comprehensive educational and ethical methodology for improving relationships among members of society. He believes that improving relationships can only be achieved by returning to the practical model embodied in the Prophet's (ﷺ) conduct, as he is the exemplar in dealing with others, gentleness, justice, reconciliation, and humility towards both young and old. He emphasizes that repairing relationships begins with repairing hearts, through instilling faith, strengthening inner conscience, and developing a sense of awareness and piety, because conduct is the fruit of belief. Sheikh (رحمہ اللہ) focused on refining the soul, controlling anger, improving morals, and being patient with the harm inflicted by others. In his view, the Prophet’s(ﷺ) biography, is a school for creating a balanced person who treats his family and community well. He explains that the Prophet, (ﷺ) established a refined society through mercy, not violence, and reformed souls through tolerance, forgiveness, and kindness. This is the basis for reforming relationships within the family and society. He emphasized the justice of the Messenger(ﷺ) in all his dealings: between his wives, his companions, and his family, which makes justice an important pillar in reforming social relations. He points to the style of the Messenger(ﷺ)in addressing his companions and his family with kind and refined words, and calming souls. Taking into account everyone’s feelings, which reflects the importance of constructive dialogue in the life of a Muslim. He explains that the Prophet’s (ﷺ) methodology in reform was truly practical, dealing with situations in a manner appropriate to the time, place, and circumstances, far from rigidity and excessive leniency. In conclusion, Sheikh Nadawi’s methodology in addressing the reform of social interaction in the Prophet’s (ﷺ) biography is based on reviving the Muhammadan model of mercy, morality, justice, and building the human being from within. It is an educational methodology that aims to reform the individual and society together through the biography as a way of life. Keywords: Methodology, social interaction, purification, reforms, Muhammadan model, dialogue, circumstances.